2019
DOI: 10.1038/s41467-019-12671-y
|View full text |Cite
|
Sign up to set email alerts
|

Intronic ATTTC repeat expansions in STARD7 in familial adult myoclonic epilepsy linked to chromosome 2

Abstract: Familial Adult Myoclonic Epilepsy (FAME) is characterised by cortical myoclonic tremor usually from the second decade of life and overt myoclonic or generalised tonic-clonic seizures. Four independent loci have been implicated in FAME on chromosomes (chr) 2, 3, 5 and 8. Using whole genome sequencing and repeat primed PCR, we provide evidence that chr2-linked FAME (FAME2) is caused by an expansion of an ATTTC pentamer within the first intron of STARD7. The ATTTC expansions segregate in 158/158 individuals typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 46 publications
5
119
0
Order By: Relevance
“…For example, expansion of (CAG) n repeats in 13 different genes causes SCAs. Similarly, recently discovered expansions of (TTTTA) n (TTTCA) m repeats in the introns of five different genes are all linked to FAME (32,(67)(68)(69). Therefore, researchers have proposed toxic gain-offunction mechanisms, which could be either at the RNA or protein levels.…”
Section: From Expanded Dna Repeats To Diseasementioning
confidence: 99%
“…For example, expansion of (CAG) n repeats in 13 different genes causes SCAs. Similarly, recently discovered expansions of (TTTTA) n (TTTCA) m repeats in the introns of five different genes are all linked to FAME (32,(67)(68)(69). Therefore, researchers have proposed toxic gain-offunction mechanisms, which could be either at the RNA or protein levels.…”
Section: From Expanded Dna Repeats To Diseasementioning
confidence: 99%
“…Giant somatosensory-evoked potential and long-latency cortical reflex can be detected by electromyography in patients with BAFME, which collectively support the cortical origin of the cortical tremor (3). Seven subtypes have been reported so far, including BAFME1 (8q24, OMIM 601068) (4), BAFME 2 (2p11.1-q12.2, OMIM 607876) (5), BAFME 3 (5p15.31-p15.1, OMIM 613608) (6), BAFME 4 (3q26.32-3q28, OMIM 615127) (7), BAFME 5 (1q32.1, OMIM 615400) (8), BAFME 6 (16p12.1, OMOM 618074) (4), and BAFME 7 (4q32.1, OMIM 618075) (4). Thus, BAFME showed genetic heterogeneity among different families.…”
Section: Introductionmentioning
confidence: 55%
“…Subsequently, TTTCA repeat insertions in an intron of YEATS2 in BAFME 4 was confirmed in a Thailand pedigree (7). ATTTC repeat expansions in STARD7 and unstable TTTTA/TTTCA expansions in MARCH6 were also found in European families (5,6). Here, we performed mutation analysis in a new BAFME family from central China and detected whether abnormal insertion of TTTTA and TTTCA expansions were associated with this BAFME pedigree.…”
Section: Introductionmentioning
confidence: 76%
“…Recent discoveries have highlighted the importance of complex pathogenic repeat expansions involving non-reference insertions (Sato et al 2009;Seixas et al 2017;Ishiura et al 2018;Corbett et al 2019;Florian et al 2019;Yeetong et al 2019) . EHdn is currently the only method capable of discovering these expansions from BAM or CRAM files without the need for re-alignment of the supporting reads.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent discoveries have shown that many pathogenic repeats have complex structure and hence require more flexible methods. For instance: (a) REs causing spinocerebellar ataxia types 31 and 37, familial adult myoclonic epilepsy types 1, 2, 3, and 4, and Baratela-Scott syndrome (Sato et al 2009;Seixas et al 2017;Ishiura et al 2018;Corbett et al 2019;Florian et al 2019;Yeetong et al 2019;LaCroix et al 2019) occur within an inserted sequence relative to the reference; (b) expanded repeats recently shown to cause spinocerebellar ataxia, familial adult myoclonic epilepsy, and cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome have different composition relative to the reference STR (Sato et al 2009;Seixas et al 2017;Ishiura et al 2018;Corbett et al 2019;Florian et al 2019;Yeetong et al 2019) ; (c) Unverricht-Lundborg disease, a type of progressive myoclonus epilepsy, is caused by an expansion of a dodecamer (12-mer) repeat (Lalioti et al 1997) . None of the existing methods are capable of discovering all of these REs.…”
Section: Introductionmentioning
confidence: 99%